ChemInform Abstract: The ′Sub′ Metallide Oxide Hydrides Sr21Si2O5H12+x and Ba21M2O5H12+x (M: Zn, Cd, Hg, In, Tl Si, Ge, Sn, Pb, As, Sb, Bi). Issue 8 (February 2015) - Jehle, Michael; Hoffmann, Anke; Kohlmann, Holger; Scherer, Harald; Roehr, Caroline
Abstract The title compounds are synthesized from melts of composition A:M:O:H = 21:2:5:24 (A: Sr, Ba; M: Zn, Cd, Hg, In, Tl Si, Ge, Sn, Pb, As, Sb, Bi) using BaH2/SrH2 as hydrogen sources.